2016
DOI: 10.1155/2016/3549878
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Poststroke Shoulder Pain: A Systematic Review and Meta‐Analysis

Abstract: Objective. To summarize and evaluate evidence for the effectiveness of acupuncture in relieving poststroke shoulder pain. Methods. Seven databases were searched without language restrictions. All randomized controlled trials that evaluated the effects of acupuncture for poststroke shoulder pain compared with controls were included. Assessments were performed primarily with the Visual Analogue Scale (VAS), Fugl-Meyer Assessment (FMA), and effective rates. Results. In all, 188 potentially relevant articles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The incidence of adverse effects of acupuncture is substantially lower than those of other medical treatments for pain reduction ( 60 ). Of the two existing reviews of acupuncture, both investigated the effects on pain reduction, and one also investigated the effects on upper extremity function ( 17 ). Although consistent with these two reviews, the findings of our systematic review must be interpreted with caution due to the high level of heterogeneity among the acupuncture therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of adverse effects of acupuncture is substantially lower than those of other medical treatments for pain reduction ( 60 ). Of the two existing reviews of acupuncture, both investigated the effects on pain reduction, and one also investigated the effects on upper extremity function ( 17 ). Although consistent with these two reviews, the findings of our systematic review must be interpreted with caution due to the high level of heterogeneity among the acupuncture therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A narrative summary of the findings was presented, and no single estimate of the effects of acupuncture was provided. A second systematic review with meta-analysis on the same topic included 12 trials and 1,002 participants ( 17 ). Both reviews found that acupuncture was associated with potential benefits in reducing PSP.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, pain control was more considerable in EAC group. Mechanism of action of acupuncture regarding pain improvement in shoulder muscles has been discussed earlier [41,43]. In addition, several studies have demonstrated that acupuncture exerts a beneficial effect on ischemic stroke through modulation of different mechanisms originating in the CNS such as regulation of cerebral blood flow in the ischemic area, antiapoptosis in the ischemic area, and regulation of neurochemicals [12].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao, et al [26] observed a considerable improvement in pain severity and shoulder ROM using VAS in patients treated with acupuncture compared to control group. However, Li and Lee [16,43] noted that although there was some evidence of efficacy of acupuncture in treatment of HSP, the results were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these reviews evaluate the efficacy of a single category of therapeutic technique, such as CIMT,25–29 robot-assisted therapy,30–35 bilateral training,36 37 task-oriented training,38 exercise therapy,39 functional electrical stimulation (FES),40 41 orthotics,42 43 mental practice,44 45 mirror therapy,46 47 action observation,48 non-invasive cerebral stimulation,49–52 brain-computer interface,53 54 virtual reality,42 home‐based therapy programmes55 and so on. There are also some comprehensive systematic reviews on general function treatment of upper limb after stroke56–58 or other specific problems, such as motor dysfunction,59 60 sensory impairment,61 spasticity,62 63 decreased quality of life,64 and shoulder pain and subluxation 65–67. In addition, other important issues of upper limb rehabilitation after stroke, like timing of intervention,68 dose of training,69 effects of severity on motor recovery,24 outcome measures70–75 and predictors of functional restoration76 77 were systematically reviewed as well.…”
Section: Introductionmentioning
confidence: 99%